Analysis of the Most Valued Organization to Work for in Spain, According to Nationality and Location - Seoane, Francisco Jesús Ferreiro; Campo Villares, Manuel O. D. (Technology Transfer and Entrepreneurship (Discontinued), 2018)
Background: The objective of this article is to analyse if there are significant relationships between the most valuable companies operating in Spain regarding professional performance, according to nationality and location within their Autonomous Communities or any superior aggrupation. To do that, a sample of 100 companies has been selected. Methods: The methodology followed is based on the selection of the 100 highestvalued companies from the point of view of Human Resources' policy for the period 2013-2016 and through the measurement of six factors: Talent Management, Retribution, Work environment, CSR, Training and Employees' perception, and classified by nationality and location. The study was based on 12 hypotheses, using the Unifactorial Variance's Analysis, Pearson correlations and regressions. One limitation could be the fact that this study refers to a particular period, focusing on Spain and the variables mentioned, based on questionnaires. The added value of this work lies on the newness as it has a quantitative character, and on the fact that most of the hypotheses do not comply. Results and Conclusion: This allows to deny certain beliefs that affirm that European and American companies operating in Spain are more attractive than the Spanish or the Mediterranean ones.
Keywords: human resources